(untitled) - Lin, Grace (Watertown, MA, 2023)
"While looking for the eggs that the chickens laid, Mei searches all over her yard. Teaches young readers about spatial sense"--
Ages 0-3.
Keywords: Fiction; Fiction; Eggs; Fiction; Mathematics; Space perception; Juvenile literature; Eggs; Juvenile literature; Mathematics; Juvenile literature; Space perception; Picture books; Board books